2021
DOI: 10.1002/pol.20210789
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization‐driven self‐assembly of semicrystalline block copolymers and end‐functionalized polymers: A minireview

Abstract: Self-assembly has been a powerful method to fabricate the polymer materials with well-defined structures and morphologies. Such assembled materials have shown wide potential applications in many fields such as nanomaterial, nanomedicine, lithography, and microelectronic. Crystallization has been a general behavior of stereoregular polymers. Besides the various noncovalent interactions, crystallization of polymer blocks or end groups can be an efficient way to manipulate the self-assembly pathway and assembled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 135 publications
1
9
0
Order By: Relevance
“…Such interactions effectively overrule the packing parameter p as the main criterion defining NP morphology. The overall concept shows resemblance to crystallization‐driven self‐assembly (CDSA), which readily allows the formation of non‐spherical NPs and more complex, hierarchical assemblies during conventional solvent exchange self‐assembly 32,33 …”
Section: Advances Of Pisa For Potential Future Ddsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interactions effectively overrule the packing parameter p as the main criterion defining NP morphology. The overall concept shows resemblance to crystallization‐driven self‐assembly (CDSA), which readily allows the formation of non‐spherical NPs and more complex, hierarchical assemblies during conventional solvent exchange self‐assembly 32,33 …”
Section: Advances Of Pisa For Potential Future Ddsmentioning
confidence: 99%
“…The overall concept shows resemblance to crystallization-driven self-assembly (CDSA), which readily allows the formation of non-spherical NPs and more complex, hierarchical assemblies during conventional solvent exchange self-assembly. 32,33 Imprinting directionality via hydrogen-bonding can be effectively realized by introducing a supramolecular moiety, such as a bis-urea sticker at the (CTA) chain end. Mellot et al 194 demonstrated that this modification leads to fiber-like morphologies over a wide range of block lengths for the core-forming block.…”
Section: Additional Intra-/intermolecular Interactions To Imprint Dir...mentioning
confidence: 99%
“…39 P2VP coronas have been grown from polyferrocenyldimethylsilane cores 40 using crystallization-driven self-assembly. 41 These micellar brushes form by hydrogen bonding or electrostatic interaction to a variety of surfaces and have been functionalized to demonstrate, for example, the separation of an oil from an aqueous emulsion.…”
Section: Alternatives To Grafting-from Techniquesmentioning
confidence: 99%
“…In the last decades, great efforts have been made in the study of self-assembly of block copolymers (BCPs) since the spontaneous packing of polymeric chains via bottomup strategy offer a promising route to prepare periodically ordered BCP nanomaterials with advanced applications in biomedicine, catalysis, separation, electronic and optical sensors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] When the BCPs are assembled in bulk state, the internal microphase separation behavior mainly depends on polymer volume fraction, polymerization degree, and Flory-Huggins interaction parameter. 10,[15][16][17][18][19] Compared with the bulk self-assembly, it has been found that a large numbers of unique BCP nanostructures (e.g., helices, stacked-doughnuts, and nanotubes) can be acquired when the BCPs are confined in specific templates or particular geometries (e.g., anodic aluminum oxide, silicon templates, track-etched membranes, patterned perfluoropolyether mold, and polydimethylsiloxane stamp).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, great efforts have been made in the study of self‐assembly of block copolymers (BCPs) since the spontaneous packing of polymeric chains via bottom‐up strategy offer a promising route to prepare periodically ordered BCP nanomaterials with advanced applications in biomedicine, catalysis, separation, electronic and optical sensors 1–14 . When the BCPs are assembled in bulk state, the internal microphase separation behavior mainly depends on polymer volume fraction, polymerization degree, and Flory‐Huggins interaction parameter 10,15–19 .…”
Section: Introductionmentioning
confidence: 99%